2020
DOI: 10.13057/biodiv/d210650
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of Fusarium spp. isolated from maize kernels in Java and Lombok, Indonesia

Abstract: Abstract. Widiastuti A, Karlina ML, Dhanti KR, Chinta YD, Joko T, Suryanti, Wibowo A. 2020. Morphological and molecular identification of Fusarium spp. isolated from maize kernels in Java and Lombok, Indonesia. Biodiversitas 21: 2741-2750. Fungal contamination of maize is a serious problem in Indonesia. Fusarium spp. infect maize in the field will be continuing to contaminate in the post-harvest period even though disease symptoms are not always emerged. Some Fusarium spp. produced mycotoxins which are harmful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The same species were recorded in this study. Some Fusarium species, such as F. verticillioides, F. proliferatum, F. oxysporum, F. bullatum and F. thapsinum were recovered from maize ears collected from 11 different geographic regions in Iran during 2004 and 2005 [30] , while in Indonesia, a research study found four species of mycotoxigenic Fusarium species isolated from maize based on molecular identification, which were Fusarium verticillioides, F. proliferatum, F. graminearum and F. asiaticum [41] . This study found that the occurrence of F. verticillioides in corn fields in the Kurdistan region was most commonly compared to other isolated species; this finding is consistent with those studies carried out in other countries such as Iran, India, Indonesia [37,36,30] , and not agree with the results reported by research carried out in Egypt, which F. oxysporum is the most common species [34] .…”
Section: Morphological Identification Of Fusarium Speciesmentioning
confidence: 99%
“…The same species were recorded in this study. Some Fusarium species, such as F. verticillioides, F. proliferatum, F. oxysporum, F. bullatum and F. thapsinum were recovered from maize ears collected from 11 different geographic regions in Iran during 2004 and 2005 [30] , while in Indonesia, a research study found four species of mycotoxigenic Fusarium species isolated from maize based on molecular identification, which were Fusarium verticillioides, F. proliferatum, F. graminearum and F. asiaticum [41] . This study found that the occurrence of F. verticillioides in corn fields in the Kurdistan region was most commonly compared to other isolated species; this finding is consistent with those studies carried out in other countries such as Iran, India, Indonesia [37,36,30] , and not agree with the results reported by research carried out in Egypt, which F. oxysporum is the most common species [34] .…”
Section: Morphological Identification Of Fusarium Speciesmentioning
confidence: 99%